Audio Quality X Accessibility How Digital Technology Changed the Way We Listen and Consume Popular Music - Gomes, Ricardo Milani (Revista Vórtex, 2016)
Based on the studies of Milner (2009), Katz (2004) and Wikstrom (2009), the article explores in details how the experience of listening and consuming music has been changing through the years due to the appearance and evolution of digital audio technology; analyzing the consequences in the recording industry and specially in its main product: popular music. The work approaches two different steps of this evolution (Compact Disks and Mp3) in terms of formats, devices and delivery methods; and how each one of them had an influence in our relationship with music.